Post Mortem Organ Weight at Bhayangkara Pekanbaru Polda Riau Hospital, Indonesia - Citra Manela1 , Biomechy Oktomalio Putri2 , Majesty Anita Imran3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Post mortem organ weight is one of indicator that serves as supporting evidence in determining the cause of death, because if there is a difference between the post mortem organ weight with normal organ weight indicates the occurrence of pathological conditions that may be related to the cause of death. The objective of this study was to determine post mortem organ weight in autopsy cases at Bhayangkara Pekanbaru Polda Riau Hospital in 2017-2018. This research is a retrospective descriptive study using secondary data. Data were obtained from autopsy data in the forensic section of Bhayangkara Pekanbaru Polda Riau Hospital in 2017-2018. Data were analyzed by using univariate analysis carried out on each variable of the research results. The results of this study were obtained from twenty one autopsy cases with a mean value of organ weight: the brain (1334.29 grams), liver (1130.90 grams), right lung (370.48 grams), left lung (311.24 grams) gram), heart (275.33 grams), left kidney (114.52 grams), right kidney (114.00 grams), and spleen (113.43 grams). Organs in men are heavier than women, except the liver. Organ weight has decreased in old age. People with short bodies tend to have lighter organ weights than people with tall bodies. The conclusion of this study is the average value of post mortem organ weight in this study is different from the weight value of organs found in forensic textbooks.